2018
DOI: 10.1039/c8cp02962h
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum and Fenton reaction: how can the reaction be modulated by speciation? A computational study using citrate as a test case

Abstract: The pro-oxidant ability of aluminum is behind many of the potential toxic effects of this exogenous element in the human organism. Although the overall process is still far from being understood at the molecular level, the well known ability of aluminum to promote the Fenton reaction is mediated through the formation of stable aluminum-superoxide radical complexes. However, the properties of metal complexes are highly influenced by the speciation of the metal. In this paper, we investigate the effect that spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…[44,45] Most of the Al +3 present in the human organism is not free in solution, but forms stable complexes with low/high molecular mass biomolecules, being around 90% of the aluminium in the blood serum bounded to the transferrin protein. [46] Concerning the Fe +3 , it is widely reported that iron oxides (e.g. Fe3O4, Fe2O3) can induce the ROS production through the Fenton reaction (catalyzing the H2O2 reaction), showing high reactivity with biological molecules such as lipids, proteins and DNA.…”
Section: Nanomof Immune Fingerprint: An Innate and Adaptive Immunity Tour Innate Immunity Tour: Chess Openingmentioning
confidence: 99%
“…[44,45] Most of the Al +3 present in the human organism is not free in solution, but forms stable complexes with low/high molecular mass biomolecules, being around 90% of the aluminium in the blood serum bounded to the transferrin protein. [46] Concerning the Fe +3 , it is widely reported that iron oxides (e.g. Fe3O4, Fe2O3) can induce the ROS production through the Fenton reaction (catalyzing the H2O2 reaction), showing high reactivity with biological molecules such as lipids, proteins and DNA.…”
Section: Nanomof Immune Fingerprint: An Innate and Adaptive Immunity Tour Innate Immunity Tour: Chess Openingmentioning
confidence: 99%
“…This early-onset form of Alzheimer’s disease is rare and mutations typically found in the amyloid precursor protein (APP) and presenilin (PSEN) genes exacerbate the formation of the neurotoxic and pathologically related peptide, amyloid-β 42 (Goate et al 1991; Sherrington et al 1995; Pimplikar 2009). Subsequently, the peptide undergoes self-aggregation forming senile plaques that deposit in fAD tissues that are sinks for metal ions including aluminium and iron (Khan et al 2006; Yumoto et al 2009; Exley and House 2011; Mirza et al 2017; Mujika et al 2018). Therefore, direct fluorescent labels allowing for the unequivocal detection of aluminium in senile plaques and related neuropathological hallmarks of Alzheimer’s disease are of pertinent interest (Mirza et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that the presence of Al and Fe in the media could enhance the root growth inhibition, probably by catalyzing ROS production ( Muller et al, 2015 ; Balzergue et al, 2017 ; Mora-Macias et al, 2017 ; Zheng et al, 2019 ). In a first study ( Ruipérez et al, 2012 ), Al was found to have a pro-oxidant effect by promoting the Fenton reaction, however, a second computational study focused on citrate ( Mujika et al, 2018 ) showed that in one hand, when Al is chelated to citrate it can have a pro-oxidant effect by stabilizing aluminum superoxide complexes but on the other hand, the chelation of Fe by citrate prevents the Fenton reaction. Thus, the authors concluded that citrate can have both promotor and protective roles in the Fenton reaction depending on multiple factors, such as the initial concentration of elements.…”
Section: Discussionmentioning
confidence: 99%